Pemberdayaan Kelompok Pembudidaya Lele di Desa Curug, Gunung Sindur, Bogor - Kusumajanti Kusumajanti; Asep Kamaluddin Nashir; Ni Putu Eka Widiastuti (Universitas Mathla'ul Anwar Banten, 2021)
EMPOWERMENT OF CATFISH FARMERS GROUP IN CURUG VILLAGE, GUNUNG SINDUR, BOGOR. Catfish farming ini Curug Village, Gunung Sindur District, Bogor Regency is carried out independently. Selling fish farming products to local markets by bringing in fish buyers (Tengkulak). The problem that occurs is that the selling price of catfish offered by collectors ranges from Rp. 17,500 – Rp. 18,000/kg. The procedure for selling fish is a problem in itself for cultivators, such as low selling prices, inappropriate weighing results. Based on these problems, the PkM team proposed efforts to empower farmers in groups, with the aim of developing a Product Marketing Strategy. The method used by direct assistance with processed products, formulating marketing strategies, targeting the local market. Empowerment of the “Curug Mutiara” catfish Cultivators in collaboration and synergy with other groups, village officials, and related agencies in Bogor Regency to achieve optimal results.